Legal and Forensic Aspects of Working with Electronic Documents Generated by Artificial Intelligence - Gabro, Oleksandr (Problems of legality, 2026)
The relevance of the research is due to the rapid development of artificial intelligence (AI) technologies and their integration into the process of creating electronic documents, which creates significant problems in the legal and forensic fields, particularly regarding the admissibility of such documents as evidence. The purpose of the article is to highlight the legal and forensic challenges associated with the attribution, probative value, and establishment of liability for electronic documents generated by AI. Methods of analysis included systemic, comparative-legal, formal-legal, and forensic methods for the study of electronic evidence. The results obtained indicate the need to develop new approaches to assessing the reliability and relevance of electronic documents created by AI, as well as the implementation of specialized forensic techniques to establish their origin and possible intervention. Particular attention is paid to attribution issues, as there is no direct liability for the actions of AI. The prospects for further research are related to the development of unified international standards for working with AI-generated evidence and the improvement of national procedural legislation.